Diversification and integration in the Philippines fishery sector Implication for microenterprise development, effeciency, equity and environmental sustainability. - Pabuayon, I.M., Musa, D.M. and Espanto, L.H (PCAMRD, 1998)
Policy Paper Series No. 98-02